2015
DOI: 10.1152/ajpendo.00526.2014
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in the uterine artery precede the hypertensive phenotype in a transgenic model of hypertensive pregnancy

Abstract: The pregnant female human angiotensinogen (hAGN) transgenic rat mated with the male human renin (hREN) transgenic rat is a model of preeclampsia (TgA) with increased blood pressure, proteinuria, and placenta alterations of edema and necrosis at late gestation. We studied vascular responses and the role of COX-derived prostanoids in the uterine artery (UA) at early gestation in this model. TgA UA showed lower stretch response, similar smooth muscle ␣-actin content, and lower collagen content compared with Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…NO produced by eNOS relaxes blood vessels, inhibits proliferation of vascular smooth muscle cells, inhibits platelet aggregation and maintains normal vascular tension and arterial blood pressure. However, in hypertension, atherosclerosis and other pathological conditions, the NO produced by eNOS cannot maintain the normal tension of blood vessels on its own; iNOS can activate and produce relatively large amounts of NO, so blood pressure does not increase malignancy [40,41]. In this study, OPO could also increase nNOS and eNOS expression levels and reduce iNOS expression in hypertensive rats.…”
Section: Discussionmentioning
confidence: 60%
“…NO produced by eNOS relaxes blood vessels, inhibits proliferation of vascular smooth muscle cells, inhibits platelet aggregation and maintains normal vascular tension and arterial blood pressure. However, in hypertension, atherosclerosis and other pathological conditions, the NO produced by eNOS cannot maintain the normal tension of blood vessels on its own; iNOS can activate and produce relatively large amounts of NO, so blood pressure does not increase malignancy [40,41]. In this study, OPO could also increase nNOS and eNOS expression levels and reduce iNOS expression in hypertensive rats.…”
Section: Discussionmentioning
confidence: 60%
“…It is important to note, however, that NO still plays a role in the vasodilation of the placental vasculature. Indeed, endothelium‐independent vasodilation, expressed as the vasodilatory response to the NO donor SNP, although reduced, was still present in preeclamptic placental vessels . This indicated that it might be the smooth muscle portion of the NO‐dependent vasodilatory pathway that is altered in preeclamptic vessels.…”
Section: Impaired Vasodilation In Pe Could Be Related To Decreased α2mentioning
confidence: 99%
“…NO is a principal vasodilator released by ECs and diffuses to the underlying VSMC layer triggering vasorelaxation . Because of its potency in mediating vasorelaxation, several studies aimed at understanding the role of NO in the isolated UA of PE animal models and in human placental vessels . However, these studies have revealed inconsistent results with controversy regarding the presence or absence of NO‐induced vasodilation in PE.…”
Section: Impaired Vasodilation In Pe Could Be Related To Decreased α2mentioning
confidence: 99%
See 2 more Smart Citations